Academic Staff Performance in the Post Covid-19: Study of Motivation, Work Environment, and Discipline - Sumarni, Tri; Yuliana, Lia; Mamengko, Rullyana Puspitaningrum (Jurnal Economia, 2024)
AbstractThe study examines how motivation, work environment, and discipline affect academic staff performance at Universitas Negeri Yogyakarta (UNY) following the COVID-19 pandemic. Using parametric statistics, it involved 191 participants in this ex-post facto quantitative research study. According to the study, motivation, work environment, and discipline all positively and significantly affect the performance of the UNY academic staff. The novelty of this study is that when employees switch from working from home to the office, it affects their motivation, the work environment, and their ability to be disciplined because of worries about the virus resurfacing. The urgency of this study is that UNY is changing from a Public Service Agency to a Legal Entity State University, so to help prepare better human resources, it needs to collect actual information. The study results are explained in more detail, along with some suggestions and implications. Keywords:Motivation, Work Environment, Discipline, Work Performance, Academic Staff